Efforts To Improve Children's Cognitive Abilities In Stating Addition Results Through Natural Material Media At RA Darussalam Wedelan Bangsri - Ianah, Uswatul (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve children's cognitive abilities in conveying addition results through the use of natural materials as learning media at RA Darussalam Wedelan Bangsri. Cognitive skills, particularly in understanding addition concepts, are crucial for early childhood development. This research employs a classroom action research (CAR) method conducted in two cycles, involving planning, implementation, observation, and reflection. The subjects of the study are Group A children at RA Darussalam. Data were collected through observation, interviews, and documentation, and analyzed using a qualitative descriptive approach. The results indicate that utilizing natural materials, such as stones, leaves, and seeds, enhances children's comprehension of addition concepts and their ability to verbally express their calculations. This improvement is evident from the children's active participation in learning activities and the increased evaluation scores in each cycle. Therefore, the use of natural materials has been proven effective in enhancing children's cognitive abilities in basic mathematics learning at RA Darussalam Wedelan Bangsri.